Evaluation of area under the inhibitory curve (AUIC) and time above the minimum inhibitory concentration ( T>MIC) as predictors of outcome for cefepime and ceftazidime in serious bacterial infections - McKinnon, Peggy S.; Paladino, Joseph A.; Schentag, Jerome J. (International journal of antimicrobial agents, 2008)
The objective of this study was to evaluate the relationship of the predicted pharmacodynamic parameters 24-h area under the inhibitory curve (AUIC = area under the concentration − time curve for 24 h of dosing/minimum inhibitory concentration (AUC 0–24/MIC)) and time above the minimum inhibitory concentration ( T > MIC) with clinical and microbiological outcomes in patients with bacteraemia and sepsis treated with cefepime or ceftazidime. Pharmacokinetic and pharmacodynamic parameters were derived for 76 of 107 patients enrolled in two prospective, randomised, clinical trials comparing cefepime with ceftazidime for the treatment of sepsis with bacteraemia, lower respiratory tract infection or complicated urinary tract infection. The relationships between the pharmacodynamic parameters and outcomes were examined. Whilst no significant differences in clinical outcomes were observed between cefepime and ceftazidime, there were significant differences in the pharmacodynamic analysis. Patients with an AUIC ≥ 250 had significantly greater clinical cure (79% vs. 33%; P = 0.002) and bacteriological eradication (96% vs. 44%; P < 0.001) than patients with an AUIC < 250. Patients with T>MIC of 100% had significantly greater clinical cure (82% vs. 33%; P = 0.002) and bacteriological eradication (97% vs. 44%; P < 0.001) than patients with T>MIC of <100%. Both microbiological and clinical cure rates were suboptimal in patients receiving cefepime or ceftazidime for the treatment of serious infections if the AUIC was <250 or T>MIC was <100%.